Peran Total Quality Manajemen Dalam Meningkatkan Kualitas Output Madrasah Melalui Sistem Kontrol Mutu - Alfan Fauzi; Muhammad Mualvi Rafiuddin Asyraf; Rif’an Anas Fauzi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research is motivated by the problems and obstacles seen by researchers. The objectives of this study are 1) To determine the role of total quality management in improving the quality of madrasah output through a quality control system 2) To determine the role of total quality management in improving the quality of madrasah output through a quality control system.The method used in research is the library research method, where this method uses literature from previous researchers. This type of research uses an information collection system from in-depth data in the form of scientific works such as journals, theses, theses, books, relevant previous research results and so on which act as proportional reference material to get answers to similar problems. Total Quality Management is a systematic and practical approach and has a strategy in carrying out its programs in an organization, which prioritizes the interests of consumers. This approach aims to improve the quality of the institution, so that the process is carried out and has become a system that always makes improvements. Total Quality Management through a quality control system aims to make graduates of high quality, and qualified and able to be competitive. Improving the quality of output is not only an institutional program but also a government program